Association between vitamin D levels with IL-6 and IL-10 in umbilical cord blood of infants - Massi, Muhammad N.; Fikri, Bahrul; Putera, Azwin M.; Alfian, Sofa D.; Ridha, Nadira R.; Putri, Sri H.; Chaera, Ummi; Iskandar, Israini W.; Shimojo, Naoki (Narra Sains Indonesia, 2024)
A worldwide issue, vitamin D deficiency affects pregnant mothers and babies everywhere, including Indonesia. It involves the adaptive immune system by controlling the production of pro- and anti-inflammatory cytokines and the balance between humoral (Th2) and cell-mediated (Th1) immunity. The aim of this study was to investigate the relationship between vitamin D and the cytokines IL-6 and IL-10 in infants. It also examined the relationship between ferritin and IL-6/IL-10 in newborns. The study collected 114 umbilical cord blood samples from term-born mothers without clinical symptoms. IL-6 and IL-10 were among the cytokine profiles measured by the enzyme-linked immunosorbent assay (ELISA). SPSS was used for statistical analysis, and an in-silico investigation was carried out to examine the molecular relationships between vitamin D and IL-6/IL-10. Using the 20 ng/mL as the cut-off for vitamin D insufficiency suggested the insignificant association of vitamin D with IL-6 (p=0.42), IL-10 (p=0.76), and ferritin (p=0.47). When the umbilical cord vitamin D level was categorized into four quartiles, the association with the highest statistical significance (quartile 4 versus quartile 2) was observed for IL-6 (p<0.001), IL-10 (p<0.001), and ferritin (p<0.001). However, the linear regression did not suggest the significant correlations of vitamin D with IL-6 (p=0.40) and IL-10 (p=0.45). A significant correlation based on the linear regression was found between ferritin and IL-10 (p=0.03). Molecular docking studies demonstrated binding affinities of -8.04 kcal/mol for IL-6-vitamin D and -8.53 kcal/mol for IL-10-vitamin D complexes, with stable root mean square deviation throughout the simulations. This study contributes valuable insights into the clinical and computational analysis of the relationship of vitamin D with IL-6 or IL-10.